Peripheral arterial disease in the Middle East: Underestimated predictor of worse outcome - El-Menyar, Ayman (Bloomsbury Qatar Foundation Journals, 2013)
Peripheral arterial disease (PAD) is a common manifestation of systemic atherosclerosis and is associated with significant morbidity and mortality. The prevalence of PAD in the developed world is approximately 12% among adult population, which is age-dependent and with men being affected slightly more than women. Despite the strikingly high prevalence of PAD, the disease is underdiagnosed. Surprisingly, more than 70% of primary health care providers in the US were unaware of the presence of PAD in their patients. The clinical presentation of PAD may vary from asymptomatic to intermittent claudication, atypical leg pain, rest pain, ischemic ulcers, or gangrene. Claudication is the typical symptomatic expression of PAD. However, the disease may remains asymptomatic in up to 50% of all PAD patients. PAD has also been reported as a marker of poor outcome among patients with coronary artery disease. Despite the fact that the prevalence of atherosclerotic disease is increasing in the Middle East with increasing cardiovascular risk factors (tobacco use, diabetes mellitus and the metabolic syndrome), data regarding PAD incidence in the Middle East are scarce.